2013
DOI: 10.1111/his.12182
|View full text |Cite
|
Sign up to set email alerts
|

Claudin‐18 overexpression in intestinal‐type mucinous borderline tumour of the ovary

Abstract: Claudin-18 positivity is a specific phenotype that is characteristic of IMBTs. Frequent and diffuse expression of gastric markers, along with less frequent and usually focal expression of intestinal markers, suggests that IMBTs are essentially composed of gastrointestinal-type mucinous epithelium (gastric-type epithelium with a variable degree of intestinal differentiation).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…CDH17 encodes a liver-intestine cadherin [ 19 ] expressed in the colon and small intestine (Figure 1B ). CLDN18 encodes a gastric type adhesion molecule [ 20 , 21 ] expressed in the stomach and lung (Figure 1C ). CLDN7 encodes an intestinal-type adhesion molecule and was investigated as a comparative control for the other two markers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…CDH17 encodes a liver-intestine cadherin [ 19 ] expressed in the colon and small intestine (Figure 1B ). CLDN18 encodes a gastric type adhesion molecule [ 20 , 21 ] expressed in the stomach and lung (Figure 1C ). CLDN7 encodes an intestinal-type adhesion molecule and was investigated as a comparative control for the other two markers.…”
Section: Resultsmentioning
confidence: 99%
“…CLDN18 has been reported to encode a gastric type of claudin expressed specifically on the cell surface of the gastric foveolar epithelium [ 20 ]. CLDN18 is a superior marker for gastric differentiation and is broadly implicated in various tumors, including those of the ovary [ 21 ] and pancreaticobiliary neoplasms [ 41 , 42 ]. Notably, CLDN18 splice variant 2 (CLDN18.2) has been reported as a pan-cancer target for therapeutic antibody [ 43 46 ], and more recently a randomized phase II trial of an anti-CLDN18.2 antibody combined with first-line chemotherapy reported a clinically relevant benefit profile in patients with CLDN18.2-positive gastric and gastroesophageal junction adenocarcinoma (American Society of Clinical Oncology annual meeting 2016, Clinical trial information: NCT01630083).…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant expressions of Claudins have been reported in various carcinomas. Although Claudin expression was reported to be reduced in breast carcinoma, it was enhanced in colonic, ovarian or gastric carcinomas . Claudin‐4 was reported positive in 97% of effusion samples from patients with ovarian, lung and endometrial carcinomas, and in one patient with pancreatic carcinoma, with these carcinoma cells showing strong and diffuse immunopositivity .…”
Section: Discussionmentioning
confidence: 97%
“…Aberrant expression of a number of Claudins has been reported in various carcinomas . Claudin‐18 is detected in gastrointestinal and lung tissues and was shown to be overexpressed immunohistochemically in pancreatic and biliary duct adenocarcinomas. Although few studies reported that Claudin‐4 or Claudin‐1 expression was present in the effusion or cervical samples, to our knowledge no study has evaluated Claudin‐18 expression on alcohol‐fixed cytology smears.…”
Section: Introductionmentioning
confidence: 99%
“…CLDN9 is associated with aerobic glycolysis (Warburg effect) in gastric and endometrial cancers and is associated with poor prognosis in oesophageal cancer [ 57 , 58 ]. CLDN18 has recently been established as a normal gastric tissue marker; however, the presence of a splice variant has been documented in patients with mucinous ovarian cancers, a rare subtype with a poor outlook [ 59 , 60 ]. The over-expression of CLDN18.2 in intestinal type mucinous tissue acts as a potential biomarker of mucinous borderline ovarian tumours, distinguishing Mullerian types, where it is absent, from intestinal sub-types [ 59 , 61 ].…”
Section: Discussionmentioning
confidence: 99%